Perkembangan Sosial-emosional Siswa Broken Home di Usia Sekolah Dasar (Studi Kasus: Analisis Siswa Kelas II Mi Roudlotus Saidiyyah Semarang) - Abdun Nasir, Muhammad Fikri; Ichsan, Ichsan (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Socio-emotional Development of Broken Home Students at Elementary School Age (Case Study: Analysis of Class II Student Mi Roudlotus Saidiyyah Semarang). This study aims to (1) determine the socio-emotional development of Broken home students at MI Roudlotus Saidiyyah Semarang during the learning process, (2) determine the socio-emotional development of Broken home students at MI Roudlotus Saidiyyah Semarang when outside of class (playing), (3) knowing the teacher's efforts in developing students' socio-emotional. This study uses a qualitative research method with a case study approach. Data obtained through interviews and observations. After the data is collected then perform data reduction-data presentation-and conclude. The results of this study are, Broken home students are able to interact and communicate well, have high trust, show mutual affection, participate in cooperative activities, easy to get along with, sensitive to the environment. The child can achieve socio-emotional development in accordance with his peers with special guidance by the teacher who is in his environment. In guiding, the teacher always provides direction, encouragement, support, and stimulus so that the child is able to stimulate well.Keywords: Developmental, Socio-Emotional, Child Broken Home